Spine Surgery - Jin Chung, Kook (IntechOpen, 2012)
"Spine Surgery" is an authoritative and didactic textbook on the various fields of spine. It is written by many authors, internationally honorable experts to share their opinions with you. The chapters cover from anatomy of spine, spinal imaging technique, biology of spine, bone graft substitute, minimally invasive spinal surgery to even spinal deformity. It has many up to date results to help readers including university graduate students, medical instrumentation developers, and medical professionals including orthopaedic and neurosurgeons, rehabilitative professionals. The readers are provided with precious information and valuable guide in your daily practice.